2015
DOI: 10.1002/jhm.2526
|View full text |Cite
|
Sign up to set email alerts
|

Hospital length of stay and all‐cause 30‐day readmissions among high‐risk medicaid beneficiaries

Abstract: This study examined the association between index hospitalization characteristics and the risk of all-cause 30-day readmission among high-risk Medicaid beneficiaries using multi-level analyses. A retrospective cohort with a baseline and a follow-up period was used. The study population consisted of Medicaid beneficiaries (21-64 years) with selected chronic conditions, continuous fee-for-service enrollment through the observation period, and at least one inpatient encounter during the follow-up period (N=15,806… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
(23 reference statements)
1
22
1
Order By: Relevance
“…Longer LOS has been shown to predict readmission in previous large-scale observational studies examining inpatients within the United States. 17,18 Patients who require longer hospital stays are commonly sicker than those who require shorter hospital stays, exposing them to a higher risk for early hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Longer LOS has been shown to predict readmission in previous large-scale observational studies examining inpatients within the United States. 17,18 Patients who require longer hospital stays are commonly sicker than those who require shorter hospital stays, exposing them to a higher risk for early hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the readmission risk between diagnoses varies [ 27 , 36 ]. In this study, the most common primary diagnoses were cardiovascular diseases, both among the readmissions and the occasional hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the most common primary diagnoses were cardiovascular diseases, both among the readmissions and the occasional hospitalizations. Chopra and colleagues [ 36 ] found that persons with hospitalization due to cardiovascular diseases, diabetes and mental health conditions were more likely to have readmission within 30 days, compared to other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous observational study demonstrated that hospital readmission within 30 days for diagnoses such as heart failure, chronic obstructive pulmonary disease, acute myocardial infarction, community-acquired pneumonia, and gastrointestinal bleed decreased in conjunction with decreased LOS (from 5.44 to 3.98 days) [ 4 ]. Another study found that longer LOS for chronic conditions (e.g., coronary artery disease, congestive heart failure, and chronic kidney disease) was associated with marginally increased risk for rehospitalization (1.03, 95% confidence interval 1.02–1.04) [ 5 ]. These findings are important because hospital readmission is used as a quality indicator.…”
Section: Introductionmentioning
confidence: 99%